Deceptive Advertising with Rational Buyers - Salvatore Piccolo; Piero Tedeschi; Giovanni Ursino (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
We study a game in which two competing sellers supplying experience goods of different quality can induce a perspective buyer into a bad purchase through (costly) deceptive advertising. We characterize the equilibrium set of the game and argue that an important class of these outcomes features pooling behavior at the pricing stage while requiring low quality sellers to air false claims about their product. These claims deceive the buyer and induce a bad purchase with positive probability. Although the low-quality product is purchased with positive probability in these equilibria, the buyer's (expected) utility can be higher than in a fully separating equilibrium. This result suggests that, surprisingly, deceptive practices may actually enhance competition. Finally, we characterize the optimal deterrence by a regulatory agency that seeks to punish deceptive practices. We show that consumer surplus maximization requires lower deterrence than social welfare maximization. The analysis is robust to various extensions.
Keywords: L13; L15; L4; 330; Asymmetric Information; Bayesian Consumers; Deception; Misleading Advertising; Signaling